Investigation of the mechanical properties of aluminium oxide thin films on polymer substrates by a combination of fragmentation and scratch testing - Moghal, J; Suttle, H; Cook, A; Grovenor, C; Assender, H (2012)
This paper reports the combination of two mechanical tests on AlOx coatings on polymer film, of the kind that can be used for gas barrier layers: uniaxial fragmentation tests and nano-scratch tests. The resulting morphology of the film, as characterised by AFM at different points along the scratch test, is very informative of the nature of the coating failure, and combined with FTIR studies of the oxides can explain the observed differences in the quantitative mechanical tests. As an illustration of the capability of these methods to distinguish differences between coatings on the same substrate with the same nominal chemistry, a comparison between three AlOx coatings on polyethylene naphthalate (PEN) is made. The different films were produced in comparable conditions by direct current (DC) magnetron sputtering, radio frequency (RF) magnetron sputtering and high power impulse magnetron sputtering (HiPIMS). Clear differences were measured between the coatings. The DC film showed the greatest strain-to-failure, perhaps due to a more open structure indicated by FTIR, and the HiPIMS sample showed a less homogeneous, but better adhered, coating. © 2012.